2017
DOI: 10.1038/jhh.2016.83
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between urinary sodium with blood pressure and hypertension among a Kazakh community population in Xinjiang, China

Abstract: Urinary sodium levels are reported to be associated with blood pressure in clinical trials and epidemiology studies. Nevertheless, the public health message of reducing sodium intake in free-living community populations remains under debate. Based on an ongoing prospective study initiated in 2012 with a community-based design in Xinjiang, China, 1668 adults (⩾30 years old) were assessed in the current study for associations between urinary sodium and blood pressure and hypertension in a free-living population … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 34 publications
1
17
0
Order By: Relevance
“…Our study addressed a gap in intergroup variations in individual cardiovascular risk factor prevalence, which had several [21]. In addition to differences in genetic backgrounds, dietary intake of high salt and high fat appeared to be major environmental factors that contributed to high BP in this ethnic group, especially for Kazakh nomads; this is supported by this study and our previous study [13]. Besides rare intake of vegetable and fruit, salty air-dried meat and milk-tea were their indispensable daily food and beverage.…”
Section: Epidemic Of Cardiovascular Risk Factorssupporting
confidence: 76%
See 1 more Smart Citation
“…Our study addressed a gap in intergroup variations in individual cardiovascular risk factor prevalence, which had several [21]. In addition to differences in genetic backgrounds, dietary intake of high salt and high fat appeared to be major environmental factors that contributed to high BP in this ethnic group, especially for Kazakh nomads; this is supported by this study and our previous study [13]. Besides rare intake of vegetable and fruit, salty air-dried meat and milk-tea were their indispensable daily food and beverage.…”
Section: Epidemic Of Cardiovascular Risk Factorssupporting
confidence: 76%
“…All strokes, hemorrhagic or ischemic, had evidence of computed tomography (CT) or magnetic resonance imaging (MRI Table 6. Relationship between estimated salt intake and high BP (also see our previous publication [13]). Table 7.…”
Section: Occurrence Of Acute Cardiovascular Eventsmentioning
confidence: 99%
“…Reasons for exclusion from metaanalyses included; findings were only presented as correlation coefficients (n=16) (35, 54-56, 61, 68, 77, 78, 81, 82, 84, 86, 87, 90, 92, 96) or as standardised regression coefficients (n=4) (57,64,89,94) , the exposure variable was presented as sodium density (n=2) (12,72) or 24-hr urinary sodium excretion was reported as sodium concentration (mmol/L) (74) or on a logarithmic scale (52,58) . Of the studies included in meta-analyses, 14 were from Asia (62,63,66,69,70,73,75,76,83,85,91,97,100,101) , eight from USA (10,11,59,60,71,88,102,103) , five from South and Central America (53,65,79,80,93) , four from Europe (9,67,95,99) , one from Samoa (98) and one included data collected across four countries (e.g. Japan, USA, UK, China) (104) .…”
Section: Resultsmentioning
confidence: 99%
“…Most of these studies (24/33) reported on more than one adiposity outcome (Table S3). Outcomes which were included in separate meta-analyses were BMI (n=31) (9-11, 53, 59, 60, 63, 65-67, 69-71, 73, 75, 76, 79, 80, 83, 85, 88, 93, 95, 97-104) , weight category (n=8) (9,11,63,73,91,97,103,104) , BW (n=7) (60,65,67,71,73,93,101) , WC (n=9) (9,65,66,70,73,75,80,83,100) and abdominal obesity (n=5) (62,66,73,102,103) . Only nine studies adjusted for energy intake (9,10,59,66,73,91,(102)(103)(104) and three studies adjusted for SSB intake (9,11,103) .…”
Section: Resultsmentioning
confidence: 99%
“…Identified studies were meta‐analyses (n = 1), RCTs (n = 3), prospective cohort studies (n = 4), retrospective case–control studies (n = 1), cross‐sectional studies (n = 27), case–control studies (n = 1), post hoc analyses of RCTs (n = 2), and quasi‐experimental studies (n = 3). Three studies assessed morbidity outcomes, two studies assessed outcomes related to symptoms/quality of life/functional status, 31 studies assessed clinically relevant surrogate outcomes, including 26 that assessed blood pressure outcomes, and six studies assessed physiologic outcomes . Of these studies, only three studies met the minimum methodological criteria for detailed critical appraisal (Table ).…”
Section: Resultsmentioning
confidence: 99%